Estimation of structural firmness and efficiency of the process-oriented control system - Хімічева, Ганна Іванівна; Свідерська, Ганна Миколаївна; Колесіна, Наталія Василівна (Eastern-European Journal of Enterprise Technologies, 2012)
Methodological approaches to the construction of the two-tier model of the process oriented management system are analyzed and both mechanisms and instruments of the evaluation of its structural stability and effectiveness are presented there